Environmental awareness among the industrial workers: A study in Tangail district, Bangladesh (Journal of the Bangladesh Agricultural University, 2014)
The Principal determination of the study was to fix the extent of environmental sentience among the different classes of industrial workers. A hundred ten workers were selected through purposive sampling technique from several industries in the region of Tangail district, Bangladesh. Among the selected workers, the female respondents were 37 in number and rests of the 73 were male. The workers were asked questions to appraise their level of understanding considering environment, environmental issues, and their persuasion to solve the different environmental problems. The determinations disclosed that, majority (91.8%) of the workers have approximately general conception about environment, idea about pollution of environmental constituents, Global warming and climate change awareness. From the view of most (85.5%) of the workers, the country is most vulnerable due to environmental pollution and not executing competent rules and ordinance along with public awareness. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18228 J. Bangladesh Agril. Univ. 11(1): 159-164, 2013